Emotion Regulation and Emotion Work: Two Sides of the Same Coin? - von Scheve, Christian (Frontiers in Psychology, 2012)
This contribution links psychological models of emotion regulation to sociological accounts of emotion work to demonstrate the extent to which emotion regulation is systematically shaped by culture and society. I first discuss a well-established two-factor process model of emotion regulation and argue that a substantial proportion of emotion regulatory goals are derived from emotion norms. In contrast to universal emotion values and hedonic preferences, emotion norms are highly specific to social situations and institutional contexts. This specificity is determined by social cognitive processes of categorization and guided by framing rules. Second, I argue that the possibilities for antecedent-focused regulation, in particular situation selection and modification, are not arbitrarily available to individuals. Instead, they depend on economic, cultural, and social resources. I suggest that the systematic and unequal distribution of these resources in society leads to discernible patterns of emotion and emotion regulation across groups of individuals.